Oral Vaccination With Recombinant Vesicular Stomatitis Virus Expressing Sin Nombre Virus Glycoprotein Prevents Sin Nombre Virus Transmission in Deer Mice - Warner, Bryce M.; Jangra, Rohit K.; Griffin, Bryan D.; Stein, Derek R.; Kobasa, Darwyn; Chandran, Kartik; Kobinger, Gary P.; Safronetz, David (Frontiers in Cellular and Infection Microbiology, 2020)
Sin Nombre virus (SNV) is the major cause of hantavirus cardiopulmonary syndrome (HCPS) in North America, a severe respiratory disease with a high fatality rate. SNV is carried by Peromyscus maniculatus, or deer mice, and human infection occurs following inhalation of aerosolized virus in mouse excreta or secreta, often in peri-domestic settings. Currently there are no FDA approved vaccines or therapeutics for SNV or any other hantaviruses, therefore prevention of infection is an important means of reducing the disease burden of HCPS. One approach for preventing HCPS cases is to prevent the spread of the virus amongst the rodent reservoir population through bait vaccination. However, bait style vaccines for rodent-borne viruses have not been employed in the field, unlike those targeting larger species. Here we utilized a recombinant vesicular stomatitis virus expressing SNV glycoprotein precursor (rVSVΔG/SNVGPC) in an attempt to prevent SNV transmission. Vaccination of deer mice with rVSVΔG/SNVGPC was able to reduce viral RNA copy numbers in the blood and lungs of directly infected animals. More importantly, vaccination, either intramuscularly or orally, significantly reduced the number of transmission events in a SNV transmission model compared with control animals. This provides a proof-of-concept in which oral vaccination of deer mice results in protection against acquiring the virus following direct contact with infected deer mice. Further development of bait style vaccines for SNV or other rodent-borne viruses could provide an effective means of reducing disease burden.